M protein mediates streptococcal adhesion to HEp-2 cells. - Wang, J R (1994)
Streptococcus pyogenes adheres to human epithelial cells in vitro and in vivo. To identify adhesins, cell wall components were extracted from S. pyogenes M6 with alkali or by treatment with mutanolysin and lysozyme. HEp-2 cells were incubated with extracts of S. pyogenes M6 and then analyzed by Western blot (immunoblot) assays, using antibodies to S. pyogenes. Only one streptococcal component (62 kDa) was bound to HEp-2 cells and was identified serologically as M6 protein. Experiments with pepsin-cleaved fragments of M protein indicated that the binding site was located at the N-terminal half of the molecule. M protein was bound selectively to two trypsin-sensitive surface components, 97 and 205 kDa, of HEp-2 cells on nitrocellulose blots of sodium dodecyl sulfate-polyacrylamide gels. Tritium-labeled lipoteichoic acid bound to different HEp-2 cell components, 34 and 35 kDa, in a parallel experiment, indicating that lipoteichoic acid was not complexed with M protein and does not mediate M-protein binding. The four HEp-2 components were unrelated to fibronectin since they did not react with specific antibodies. An M-protein-deficient (M-) strain of streptococcus (JRS75), grown in chemically defined medium, showed 73% less adhesion activity to HEp-2 monolayers than an M+ strain (JRS4). Streptococcal adhesion was insensitive to competitive inhibition by selected monosaccharides. These results indicate that M protein binds directly to certain HEp-2 cell membrane components and mediates streptococcal adhesion.